Economic Integration and Forest Sector Dynamics: Türkiye’s Strategic Outlook in a BRICS-Aligned Future - Bayramoğlu, Mahmut Muhammet; Küçükbekir, Emre; Bulut, Alper; Çelik, Abdullah (MDPI AG, 2025)
The BRICS has emerged as a strategic actor in global environmental and economic governance, encompassing 42% of the world’s population, 32% of global GDP, and nearly half of the world’s forest resources. Member countries have integrated forest management with renewable energy transition and carbon market mechanisms as part of their sustainable development strategies. In this context, Türkiye positions the forestry sector as both an environmental and economic lever in its potential alignment with BRICS while seeking to diversify its foreign policy. This study examines the long-term relationships between forest area, population, forest product trade, renewable energy production, and carbon emissions in BRICS-T countries for the period 2009–2023, employing panel econometric methods (FMOLS and DOLS). The findings indicate that population growth, forest expansion, and forest product trade are associated with increased emissions, while renewable energy production contributes to emission reductions. Moreover, bidirectional causality is identified between population and emissions and between renewable energy and emissions. The results suggest that environmental sustainability depends not only on the availability of resources but also on the quality of governance, policy coherence, and sectoral coordination. The study provides an original contribution to the literature by analyzing Türkiye’s environmental and economic integration with BRICS through the combined lens of forestry and energy transition, offering exploratory policy implications for Türkiye’s strategic position in a multipolar world.